2013
DOI: 10.1089/pop.2012.0045
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Patterns of Comorbidities in the Medicare Population

Abstract: It is widely accepted that Medicare beneficiaries with multiple comorbidities (ie, patients with combinations of more than 1 disease) account for a disproportionate amount of mortality and expenditures. The authors previously studied this phenomenon by analyzing Medicare claims data from 2008 to determine the pattern of disease combinations (DCs) for 32,220,634 beneficiaries. Their findings indicated that 22% of these individuals mapped to a long-tailed distribution of approximately 1 million DCs. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…For example, Sorace et al noted that while many beneficiaries had multiple diagnoses making them more costly and riskier, these diagnoses’ combinations remained relatively stable between 2007 and 2009. 20 However, this aggregate stability in risk scores over time does not imply that individual conditions or condition categories do not vary. For example, Mu et al showed that among beneficiaries with end-stage renal disease (ESRD), the Western region of the US had the lowest score between 2006 and 2009, and the HCC score fell annually in every region.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Sorace et al noted that while many beneficiaries had multiple diagnoses making them more costly and riskier, these diagnoses’ combinations remained relatively stable between 2007 and 2009. 20 However, this aggregate stability in risk scores over time does not imply that individual conditions or condition categories do not vary. For example, Mu et al showed that among beneficiaries with end-stage renal disease (ESRD), the Western region of the US had the lowest score between 2006 and 2009, and the HCC score fell annually in every region.…”
Section: Introductionmentioning
confidence: 97%
“…First, it will be challenging to define complex patients in a way that enables the design of specific interventions: A recent study of chronic conditions among approximately 32 million Medicare beneficiaries found more than 2 million unique combinations of conditions, reflecting a very "long tail" that changes nationally over time. [7][8][9] This distribution suggests that developing interventions tailored to each combination of disease is infeasible.…”
Section: Introduction Backgroundmentioning
confidence: 99%